Proline Homeostasis in Saccharomyces cerevisiae: How Does the Stress-Responsive Transcription Factor Msn2 Play a Role? - Mat Nanyan, Noreen Suliani binti; Takagi, Hiroshi (Frontiers in Genetics, 2020)
Overexpression of MSN2, which is the transcription factor gene in response to stress, is well-known to increase the tolerance of the yeast Saccharomyces cerevisiae cells to a wide variety of environmental stresses. Recent studies have found that the Msn2 is a feasible potential mediator of proline homeostasis in yeast. This result is based on the finding that overexpression of the MSN2 gene exacerbates the cytotoxicity of yeast to various amino acid analogs whose uptake is increased by the active amino acid permeases localized on the plasma membrane as a result of a dysfunctional deubiquitination process. Increased understanding of the cellular responses induced by the Msn2-mediated proline incorporation will provide better comprehension of how cells respond to and counteract to different kinds of stimuli and will also contribute to the breeding of industrial yeast strains with increased productivity.